ARISTOTLE AND ROUSSEAU'S THOUGHTS ON CITIZENSHIP IN THE CONTEXT OF MODERN INDONESIAN DEMOCRACY - Bambang Yuniarto; Laila Zahra; Hani Fitri Yani; Muhammad Nafis Adadinur; Fadel Ibnu Firmansyah; Gita Regina Pramesti (Adisam Publisher, 2025)
This study aims to analyze Aristotle’s and Jean-Jacques Rousseau’s thoughts on the concept of citizenship and their relevance to modern Indonesian democracy. Employing a descriptive qualitative approach, the research examines the primary texts of both philosophers and situates their ideas in critical dialogue with Indonesia’s contemporary socio-political realities. For Aristotle, a citizen is one who actively participates in governance and public life to achieve eudaimonia or collective well-being. Rousseau, on the other hand, emphasizes the general will (volonté générale) as the foundation of political legitimacy, where the ideal citizen prioritizes the common good over individual interests. In the Indonesian context, these perspectives resonate with the participatory principles of Pancasila democracy, which upholds deliberation, mutual cooperation, and social justice. Nevertheless, Indonesia’s democratic practice continues to face challenges such as political apathy, oligarchic dominance, and low civic literacy. The findings suggest that a synthesis between Aristotle’s political rationality and Rousseau’s collective morality could strengthen Indonesian citizenship toward a more substantive democracy. Thus, philosophical reflection on classical concepts of citizenship provides an ethical and normative framework for enhancing a civilized and socially just democratic life in Indonesia.